Hyoid Bone Posıtıon And Orıentatıon İn Class I And Class Iı Dıvısıon 2 Malocclusıons - Zafer Sarı; Tancan Uysal; Bülent Çatalbaş; Abdullah Demir; Serdar Üşümez; Faruk Ayhan Başçiftçi (Galenos Yayinevi, 2003)
Various studies have documented a variability of hyoid bone position in relation to changed mandibular position or head posture. The aim of this study was to investigate the hyoid bone position and inclination on the cephalometric radiographs of two groups of patients exhibiting Class I normal occlusion and Class II division 2 malocclusions. This study was carried out on two groups. The first group consisted of 19 lateral cephalometric radiographs of 12 girls and 7 boys (mean age: 13.4 ± 1.5) shows skeletally and dentally Class I and normal growth pattern. The second group consisted of 19 lateral cephalometric radiographs of 14 girls and 5 boys (mean age 13.5 ± 2.2) shows skeletally and dentally Class II division 2 malocclusion. Nine sagital, 5 vertical and 5 angular, totally 21 measurements were used to determine the position of the hyoid bone, t test was performed for statistical evaluation. Method error was estimated by Dahlberg's formula. The findings revealed that in Class II division 2 patients, the hyoid bone was more retrusive in sagital plane, nearer to the upper reference plane in vertical plane, and more parallel to the ground plane. However no statistically significant differences were found. As a conclusion, there were no statistically significant differences exist between Class II division 2 patients and Class I group. Besides some insignificant differences reflects the characteristic properties of Class II division 2 patients.